Modeling the diffusion of flammable hydrogen cloud under different liquid hydrogen leakage conditions in a hydrogen refueling station. (19th July 2022) - Sun, Ruofan; Pu, Liang; Yu, Haishuai; Dai, Minghao; Li, Yanzhong
Abstract: Constructing hydrogen refueling stations will be popular for hydrogen energy use in the future, and investigating the diffusion characteristics of hydrogen in a leakage incident is quite significant. The instantaneous evolution of flammable hydrogen clouds arising from liquid hydrogen leakage in a hydrogen refueling station is predicted using Ansys Fluent, and parametric analyses are conducted to reveal the effects of storage pressure, source height, and leakage direction on the distributions of the flammable regions. In addition, the feasibilities of heating the ceiling or the ground of the station after the leakage of liquid hydrogen to accelerate the hydrogen dilution are examined. The results show that the flammable region is stabilized at 90 s, the corresponding flammable hydrogen cloud volume is about 333 m 3, and the extensions of downwind and vertical directions reach 10 m and 9.3 m. Storage pressure has a finite effect on the downwind diffusion distance of the flammable cloud. A lower source height tends to format the high-concentration hydrogen cloud near the ground while a higher source height helps separate the flammable clouds from the ground. The upward leakage direction leads to the maximum downwind diffusion distance of about 10.2 m while the downward leakage direction makes the high hydrogen concentration region confined below the ceiling. Just maintaining the ceiling at the initial temperature of 300 K is effective for accelerating the hydrogen dilution in the upward leakage. The maximum hydrogen concentration and the flammable volume can be reduced at rates of 0.35 vol % and 8% for every 50 K increase in heating temperature. For the downward leakage, keeping the ground at the initial temperature just works for the first 40 s in reducing the maximum hydrogen concentration, while increasing the heating temperature receives a gradually declined effect on reducing the flammable volume. Highlights: Storage pressure has a finite influence on hydrogen flammable regions. The separation of flammable region from the ground depends on source height. Maintaining the ceiling at 300 K is effective for the hydrogen dilution for upward leakage. Heating temperature of the ground has a critical effect on reducing the flammable volume.